Holomorphic derivatives of Siegel modular forms - Hofmann, Eric; Kohnen, Winfried (Taehan-Suhakhoe-hoebo, 2018)
In this paper, following a criterion of E. Yang and L. Yin we discuss whether on the Siegel half-space of genus g>=2 a holomorphic derivative exists.
Gesehen am 08.02.2019